Implementation of Digital Assessment Based on the Learning Platfrom ”Kahoot!” to Evaluate the Conceptual Understanding of Physic - Anestasya, Feti Fitri; Koto, Irwan; Setiawan, Iwan (Kasuari: Physics Education Journal (KPEJ), 2025)
This research has two main objectives: (1) to investigate the extent of the effectiveness of using the Kahoot! platform in evaluating students' understanding of physics concepts; and (2) to explore and understand students' perceptions regarding the use of digital assessments based on the Kahoot! platform in the context of evaluating their understanding of these physics concepts. This study falls into the category of experimental research that employs a quantitative method with a research design known as One group pretest – posttest. In its implementation, the instruments used to collect data include interviews, tests, and systematically designed questionnaires. The results of this study indicate that: (1) the analysis shows that the N-Gain scores obtained fall within the moderate criteria, indicating that the use of the Kahoot! platform is effective in evaluating students' understanding of physics concepts, thus demonstrating a significant improvement in their understanding; and (2) students' perceptions of the use of this digital assessment received a very good category. Based on these findings, it can be concluded that the use of digital assessments based on Kahoot! is not only effective in enhancing students' understanding but also highly suitable for application in the process of evaluating understanding of physics concepts, making it a beneficial alternative in the modern educational landscape.